(untitled) - Dr. Prem Bahadur Khadka (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Mark Twain is the pet name of Samuel Langhorne which he kept after writing one of his famous novels named ’A Life on Mississippi’. The novels were written by Mark Twain to show his interest in the adventures. He mostly wrote the novels which were inspired by his adventures of travels which shows that how adventure freak he was. Mark Twain is inspired by most of the writers of today’s generation. A Life on Mississippi is the autobiographies of the adventures of Mark Twain. In the novel, Mark Twain describes the past, present, and future of the Mississippi river which includes the people and their ways of lifestyle around the Mississippi river. Other novels such as The Prince and the Pauper and The Adventures of Tom Sorwey are also some remarkable novels of Mark Twain. Key words: Samuel Langhorne, Mark Twain, A Life on Mississippi, Tom Sorwey, and adventure freak